2012
DOI: 10.1364/oe.20.024175
|View full text |Cite
|
Sign up to set email alerts
|

Integral imaging based 3D display of holographic data

Abstract: We propose a method and present applications of this method that converts a diffraction pattern into an elemental image set in order to display them on an integral imaging based display setup. We generate elemental images based on diffraction calculations as an alternative to commonly used ray tracing methods. Ray tracing methods do not accommodate the interference and diffraction phenomena. Our proposed method enables us to obtain elemental images from a holographic recording of a 3D object/scene. The diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It has been shown that diffractive lenses, realised as binary masks or by reconfigurable spatial light modulators, can be used to replace conventional microlens arrays [32,33]. Although binary masks might give low diffraction efficiency, phase-only liquid crystal on silicon devices will give significantly better-quality results [5].…”
Section: A 360-degree 3d Light-field Camera Designmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that diffractive lenses, realised as binary masks or by reconfigurable spatial light modulators, can be used to replace conventional microlens arrays [32,33]. Although binary masks might give low diffraction efficiency, phase-only liquid crystal on silicon devices will give significantly better-quality results [5].…”
Section: A 360-degree 3d Light-field Camera Designmentioning
confidence: 99%
“…It can overcome conventional stereoscopic and auto-stereoscopic display limitations and many advances in this technology have been demonstrated [4]. Moreover, it has been shown that this method is indeed related to holography [5]. Light-field imaging [6][7][8] is rapidly developing as an alternative to conventional methods [9].…”
Section: Introductionmentioning
confidence: 99%